Farmed Reindeer - a future prospect? - Rehbinder, Claes; Ekberg, Bengt; Brorsson, Joel (Rangifer, 1995)
On a farm near Uppsala, reindeer, in a small scale trial (6 animals), far away from their natural grazing areas, have been kept on a pasture, four hectars in size, for more than two years, fenced in by electric wire. They have stayed healthy and borne calves. The animals have received hay and commercial supplementary feed during the winter season and have, spring and autumn, been regularly dewormed with Ivermectin pour on. They carry a very low burden of lungworms and are free of gastrointestinal worms and Oestridae.